Factors Associated to the Decision to Terminate or not an Unwanted Pregnancy among a Sample of Civil Servant in São Paulo State, Brazil. - Silvana, Ferreira Bento; Karla, Simônia de Pádua; Graciana, Alves Duarte; Maria, José Duarte Osis; Anibal, Faúndes (Journal of Public Health International, 2019)
This is a cross sectional study of a sample of civil servants from the interior of São Paulo state, carried out with the purpose of evaluating the occurrence of unwanted pregnancies, the proportion which were terminated, the reason given for having or not having an abortion and which factors were associated to the decision whether or not to terminate an unwanted pregnancy. Just over one fifth declared to have experienced an unwanted pregnancy and over half of them were aborted. The reasons to abort concentrate on interferance with their life expectancy: “to continue studying or working” “being single”, “too young to get married” and “to become a father or mother”. Also important were fear of parents and rejection by the respondents'partner. Among those who did not terminate the unwanted pregnancy religion acted as a barrier among almost one third and the legal barrier for almost one fourth. Not having a permanent partner, being in use of behavioral or barrier method of contraception and higher education were associated with higher incidence of abortion of the unwanted pregnancy, but in multiple regression, only higher education remain significantly associated. Our results showed that once the unwanted pregnancy occur, more than half of them will be aborted, confirming the need to concentrate the efforts in reducing unwanted pregnancies if we want to prevent abortion.
Keywords: Unwanted pregnancy; induce abortion; reason to abort; educational level